Karakter Manusia yang Dipimpin oleh Roh tidak Hidup di bawah Hukum Berdasarkan Galatia 5:18 - Ipan Morris Pangaribuan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2020)
Christianity believes and have faith in the Triune God. Each Person of the Trinity has different role but has the same attribute, namely both Holy, Powerful and worthy of worship. In the Christian life, Holy Spirit is another helper but of one kind as God Himself. The Holy Spirit is the Person promised by the Lord Jesus to His disciples. The Holy Spirit dwells and leads everyone who has believed in Christ and make their lives change drastically. The Spirit-led life is called ‘Life’, in the Greeks term “Peripatusin” (Peripatousin), meaning walking, in this case refers to all activities in the life of the believer.1 1 Corinthians 1:26 shows evidence of the transformation of those who have received and are led by the Holy Spirit in their hearts. Because of the leading of the Holy Spirit or the Spirit of God, the early Church grew very rapidly despite of great persecution. The Holy Spirit also reveals new and fresh truth to each generation. And through the Holy Spirit, people can repent, know and believe in Jesus (1 Corinthians 12:3) so that by the Spirit people can follow Christ’s example (2Corintians 3:18)2. The role of the Holy Spirit in leading the Church today is to liberate the Church as a whole and to give boldness to the Church in witnessing for Him.